2011
DOI: 10.1186/1472-6831-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional evaluation of the periapical status as related to quality of root canal fillings and coronal restorations in a rural adult male population of Turkey

Abstract: BackgroundTo determine the prevalence of periapical lesions in root canal-treated teeth in a rural, male adult, Turkish population and to investigate the influence of the quality of root canal fillings on prevalence of periapical lesions.MethodsThe sample for this cross-sectional study consisted of 552 adult male patients, 18-32 years of age, presenting consecutively as new patients seeking routine dental care at the Dental Sciences of Gulhane Military Medicine, Ankara. The radiographs of the 1014 root canal-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 34 publications
3
26
2
Order By: Relevance
“…In this study, an acceptable standard of treatment was found in 62 roots (9.2%) with 32.3% of them associated with signs of periapical disease. These findings agreed with Gündüz et al 8 , who found that root canal filling was rated as adequate in 425 teeth (41.9%). In the present study, the same group had a 59.8% success rate.…”
Section: 26supporting
confidence: 92%
“…In this study, an acceptable standard of treatment was found in 62 roots (9.2%) with 32.3% of them associated with signs of periapical disease. These findings agreed with Gündüz et al 8 , who found that root canal filling was rated as adequate in 425 teeth (41.9%). In the present study, the same group had a 59.8% success rate.…”
Section: 26supporting
confidence: 92%
“…There is significant evidence in scientific literature that the technical quality of root canal filling has a substantial effect on the outcome of root canal treatment 1,2 . Failed root canal filling is related to insufficient treatment, through technical error in the canal system of the tooth 3,4 . Numerous epidemiologic studies performed in many countries found a high prevalence of poor technical quality in root canal filling associated with periapical radiolucency [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the abstracts of 1097 studies were read. A total of 1022 references were excluded on the basis of their titles and/or abstracts, and 75 were selected for full analysis, but no study could be included in the present systematic review (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 75 studies selected for full analysis, 27 did not present their results by age groups, which not only made it impossible to calculate percentages of success/failure but also prevented a relationship between obturation quality and periapical health from being determined. This may be explained by the objective of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation